Motivasi Lepas Adiksi Narapidana Narkoba - Karindra, Leo Rahmat; Rohayati, Ade Cici (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2024)
The existence of family support for prisoners is very important because it produces many benefits, one of which is motivation to improve themselves. Drug prisoners are one of the prisoners who really need family support, because there is a phenomenon of addiction that is felt. This study will attempt to show the influence provided by family support on the level of motivation of prisoners, especially to escape drug addiction. The research method used is a quantitative method with a type of correlation research followed by regression analysis. The research respondents used were drug prisoners in Tulungagung Class IIB Correctional Facility with a total of 33 people. Data collection was carried out using questionnaire techniques, namely family support questionnaire and addiction release motivation questionnaire. Referring to the results of the study, it is known that the family support variable has a significant positive effect on the emergence of the variable of motivation to escape addiction in drug prisoners in Tulungagung Class IIB Correctional Facility. This result is based on the calculated t value obtained, which is 7.361. This figure is greater than the t table, which is 1,692 so that the research results accept the Ha hypothesis which means it has a significant effect. The regression equation obtained is Y = 6,691 + 0,669X which has several interpretations of meaning, namely: (1) If the family support variable = 0 (constant), then the value of the addiction release motivation variable is 6.691; and (2) Every additional value in the family support variable, there is an additional value in the addiction release motivation variable of 0,669.